Comparing two pioneers of development ethics: Louis-Joseph Lebret and Denis Goulet. Issue 2 (4th May 2021) - Culebro Juárez, Montserrat; Gasper, Des
ABSTRACT: This paper discusses the respective contributions to development ethics made by Louis-Joseph Lebret (1897–1966) and his pupil and successor Denis Goulet (1931–2006). Sections 2 and 3 present steps in the emergence of a field of development ethics, and introduce the work of Lebret and Goulet, noting similarities and contrasts. Sections 4 and 5 clarify different senses and forms of 'development ethics', to then discuss who might be called 'father of development ethics'. Lebret had devised a field of human economics and in the 1950s called for an ethics of development, which he began to sketch. His work made significant advances, especially if development ethics is seen as an interdisciplinary policy-oriented field rather than as a subdiscipline in philosophical ethics. In the 1960s, Goulet went on to outline development ethics as a philosophical subdiscipline and to articulate various themes. In his later work though, while always speaking of a 'discipline' of development ethics but mostly meaning disciplined investigation, Goulet largely pursued, as had Lebret, a path toward a policy-oriented field of 'practical ethics', not a (sub)disciplinary path in a conventional academic sense.